2020
DOI: 10.1038/s41467-020-18043-1
|View full text |Cite
|
Sign up to set email alerts
|

Understanding colossal barocaloric effects in plastic crystals

Abstract: Plastic crystal neopentylglycol (NPG) exhibits colossal barocaloric effects (BCEs) with record-high entropy changes, offering exciting prospects for the field of solid-state cooling through the application of moderate pressures. Here, we show that the intermolecular hydrogen bond plays a key role in the orientational order of NPG molecules, while its broken due to thermal perturbation prominently weakens the activation barrier of orientational disorder. The analysis of hydrogen bond strength, rotational entrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
38
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 40 publications
1
38
2
Order By: Relevance
“…Here, we evaluated the colossal BC effect associated with the L-S-T around room temperature in C n H 2 n +2 with n = 16 and 18. Only a low pressure of ~50 MPa completely drives the Δ S r of ~700 J kg −1 K −1 , which is comparable to that of commercial refrigerants 21 and prominently larger than that of plastic crystals 21 24 . Moreover, a high adiabatic temperature change (Δ T d ) of ~18 K was achieved under 100 MPa by direct measurement (i. e., direct method) 6 , which doubled when the applied pressure was increased to 200 MPa.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…Here, we evaluated the colossal BC effect associated with the L-S-T around room temperature in C n H 2 n +2 with n = 16 and 18. Only a low pressure of ~50 MPa completely drives the Δ S r of ~700 J kg −1 K −1 , which is comparable to that of commercial refrigerants 21 and prominently larger than that of plastic crystals 21 24 . Moreover, a high adiabatic temperature change (Δ T d ) of ~18 K was achieved under 100 MPa by direct measurement (i. e., direct method) 6 , which doubled when the applied pressure was increased to 200 MPa.…”
Section: Introductionmentioning
confidence: 83%
“…To date, many achievements have been made in a large variety of solid-state caloric materials, where the isothermal entropy change driven by external fields is on the order of 10–200 J kg −1 K −1 5 – 20 . Very recently, substantial progress was made in plastic crystals 21 24 . Reversible entropy changes (Δ S r ) of ~470 and 515 J kg −1 K −1 were driven by ~580 and 570 MPa in NPA and NPG, respectively 23 .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, plastic crystals have been identified as outstanding barocaloric (BC) agents [10][11][12] because they may display enormous entropy changes related to orientational disorder released across solid-to-solid phase transitions that are sensitive to mechanical stress due to associated large volume changes. In the case of plastic crystal neopentylglycol, it has been shown that, at the atomic scale, a large compressibility facilitates the shortening of the hydrogen bond length by application of pressure, thus leading to an increase of the orientational energy barrier and, therefore, to the stabilization of the ordered phase [13].…”
Section: Introductionmentioning
confidence: 99%
“…(b)Reversible adiabatic temperature changes upon 0 → ~1 kbar pressure increase as a function of temperature. Literature data taken from: PG:[12]; C60:[13];[TPrA][Mn(dca)3]:[44]; [(CH3)4N]Mn[N3]3:[45]; MnCoGeB0.03 (asterisk):[46]; (MiNiSi)0.60(FeCoGe)0.40 (diamond) and (MiNiSi)0.61(FeCoGe)0.39 (triangle):[47]; Ni50Mn31.5Ti18.5 (circle):[48].…”
mentioning
confidence: 99%
“…It is based on the gasliquid transformation that the traditional vapor-compression technology realizes the strong cooling capacity. The reported SSC effect is mainly associated with the transformation between two "solid" states with notably different degrees of lattice, spin, polar or electron ordering [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] . Therefore, it is a big challenge for SSC materials to acquire as good refrigeration performance as conventional refrigerants.…”
mentioning
confidence: 99%